Penilaian amalan pengurusan kualiti maklumat bagi sistem maklumat kesihatan - Siti Asma Mohammed (Tanjong Malim, 2014)
Penilaian amalan pengurusan kualiti maklumat bagi sistem maklumat kesihatan by Siti Asma Mohammed